CPAP and measures of cardiovascular risk in males with OSAS. - Kohler, M; Pepperell, J; Casadei, B; Craig, S; Crosthwaite, N; Stradling, JR; Davies, R (2008)
Obstructive sleep apnoea syndrome (OSAS) has been associated with hypertension, stroke and myocardial ischaemia in epidemiological and observational studies. Continuous positive airway pressure (CPAP) is the treatment of choice for OSAS, but the impact of this intervention on established risk factors for cardiovascular disease remains incompletely understood. A total of 102 males with moderate-to-severe OSAS were randomised to therapeutic (n = 51) or subtherapeutic (n = 51) CPAP treatment for 4 weeks to investigate the effects of active treatment on 24-h urinary catecholamine excretion, baroreflex sensitivity (BRS), arterial stiffness (augmentation index) and 24-h ambulatory blood pressure (ABP). After 4 weeks of therapeutic CPAP, significant reductions were seen in urine normetanephrine excretion (from mean+/-sd 179.7+/-80.1 to 132.7+/-46.5 micromol x mol(-1) creatinine) and augmentation index (from 14.5+/-11.3 to 9.1+/-13.8%) compared with the subtherapeutic control group. Furthermore, therapeutic CPAP significantly improved BRS (from 7.1+/-3.3 to 8.8+/-4.2 ms x mmHg(-1)) and reduced mean arterial ABP by 2.6+/-5.4 mmHg. In conclusion, treatment of obstructive sleep apnoea with continuous positive airway pressure may lower cardiovascular risk by reducing sympathetic nerve activity, ambulatory blood pressure and arterial stiffness and by increasing sensitivity of the arterial baroreflex.